Elastic Behavior of Lead Germanate Near Transition Temperature - Abdul Ghani, I. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
All the stiffened and unstiffened elastic constants for lead germanate (Pb5Ge3O11) single crystal have been measured from room temperature 298 K up to 513K by using ultrasonic pulse superposition technique. The correction of piezoelectric stiffening has been used to obtain the unstiffened elastic constants. Elastic moduli of lead germanate (C11, C33, C12, C13, C44 and C66) decrease with the increase of temperature. C11, C33, C12 and C13 suffered a dip at transition temperature but they increase with the increase of temperature just above Curie temperature between 453 and 473 K because of their positive temperature coefficients in this range, and then decrease slightly (except C12 increases) in the range between 473K and 513K. But for the shear elastic moduli (C44 and C66): C44 shows very slight and gradual increase and then decrease with the increase of temperature, while C66 shows a small and graduate decrease with increasing temperature. These measurements were compared with previous experimental published work.